The Humanizing Brain: An Introduction - Ashbrook, James B. (Zygon, 1999)
The rediscovery of the sacred needs to take into account the neural underpinnings of faith and meaning and also draw on the insights of the emerging discipline of complexity studies, which explore a tendency toward adaptive self-organization that seemingly is inherent in the universe. Both neuroscience and complexity studies contribute to our understanding of the brain's activity as it transforms raw stimuli into recognizable patterns, and thus “humanizes” all our perceptions and understandings. The brain is our physical anchor in the natural environment—and its human capacities orbit us into the emerging world of culture (including religion), which provides a template for the brain's function of making sense of an ambiguous reality. The humanizing brain holds together scientific causality and religious meaning, working both bottom-up (linking the physical and the experiential) and top-down (beginning with the whole of things, or God). These processes we know as “mind” (experienced as intentionality, subjective consciousness, empathy, imagination, memory, adaptability). We maintain that such processes are not only subjective but built into “the way things really are.” Thus, they carry the most privileged information about the nature of reality to which we human beings have access. For not only are we humans observers and logicians, but we are embedded in the larger reality; and as we strive to make sense of it all, we become both Homo sapiens and Homo religiosus.